2020
DOI: 10.1016/j.omtn.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

The Underlying Mechanisms of Noncoding RNAs in the Chemoresistance of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most lethal human malignancies. Chemotherapeutic agents, such as sorafenib and lenvatinib, can improve the outcomes of HCC patients. Nevertheless, chemoresistance has become a major hurdle in the effective treatment of HCC. Noncoding RNAs (ncRNAs), including mircoRNAs (miRNAs), long ncRNAs (lncRNAs), and circular RNAs (circRNAs), have been demonstrated to participate in the onset and progression of HCC. Moreover, multiple lines of evidence have indicated that ncRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 131 publications
1
28
0
Order By: Relevance
“…In addition, overexpression of miR-1324 reverses circFoxM1-induced sorafenib resistance and increases MeCP2 expression. This further confirms that circFOXM1 contribute to the regulation of sorafenib sensitivity in HCC cells through the miR-1324/MeCP2 axis (95).…”
Section: Circrnas and Sorafenib Resistance Of Hccsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, overexpression of miR-1324 reverses circFoxM1-induced sorafenib resistance and increases MeCP2 expression. This further confirms that circFOXM1 contribute to the regulation of sorafenib sensitivity in HCC cells through the miR-1324/MeCP2 axis (95).…”
Section: Circrnas and Sorafenib Resistance Of Hccsupporting
confidence: 76%
“…However, studies on the role of circRNAs in the sorafenib resistance of HCC are still in the infancy. It has been found 582 differentially expressed circRNAs in HCC cells resistant to sorafenib (HUH7-S), of which 272 were up-regulated and 310 were down-regulated, with a statistically significant difference (0.05) (95). This suggests that circRNAs with different expression levels may exert a crucial role in sorafenib resistance of HCC.…”
Section: Circrnas and Sorafenib Resistance Of Hccmentioning
confidence: 99%
“…To date, the conventional chemotherapy treatments in patients with HCC are still not ideal due to the frequently occurring chemoresistance [22,23]. A growing number of studies have showed that the exiting of cancer stem cells and their enrichment during chemotherapy is closely associated with chemotherapy failure and HCC relapse [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the conventional chemotherapy treatments in patients with HCC are still not ideal due to the frequently occurring chemoresistance (21,22). A growing number of studies have showed that the exiting of cancer stem cells and their enrichment during chemotherapy is closely associated with chemotherapy failure and HCC relapse (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%